Cultural and political dimensions of the U.S. census - Riche, Martha Farnsworth (1999)
The census is repeatedly the focus of cultural debate and conflict because its relatively precise quantification of who we are codifies the shift from who we have been to who we are becoming. The census both symbolizes and concretizes these fundamental changes because the census's constitutional purpose is to distribute power (and public money) equally, both geographically and by population. In other words, the census is a built-in safeguard against the maintenance of power by a no-longer dominant group. However, shifting cultural perceptions and values, not just shifts in numbers, are played out in political debates over the census. - Reproduced
Keywords: United States - Population; United States - Census; Population censuses